Large-scale cultivation of Leishmania infantum promastigotes in stirred bioreactor - Aydogdu, M.; Bagirova, M.; Allahverdiyev, A.; Abamor, E. S.; Ozyilmaz, O. A.; Dinparvar, Sahar; Kocagoz, T. (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Background \& objectives: Bioreactors are practical tools that are used for economical, time-conserving and large-scale production of biomass from cell cultivation. They provide optimal environmental conditions such as pH and temperature required for obtaining maximum amounts of biomass. However, there is no evidence in the literature on the large-scale cultivation of Leishmania infantum parasites in the bioreactor. Therefore, the present study was undertaken to develop a new approach for obtaining L. infantum biomass by using pH and temperature controllable stirred bioreactor and to compare parasitic growth kinetics with classical method within erlenmeyers. Methods: In order to obtain parasite biomass, a newly developed pH and temperature controlled stirred bioreactor was used and its efficacy was compared with a graduated classical scale-up method. Growth kinetics of parasites within erlenmeyers and bioreactors were determined by evaluating promastigote numbers using haemocytometer. The graduated scale enlargement of culture was followed by T25 flask, T75 flask, and 1 L erlenmeyer, respectively. Results: Obtained results showed a 10-fold increase in the number of promastigotes within the conventional culture performed in 700 ml medium, while parasite numbers increased approximately 15 times due to initial inoculation amounts in the bioreactor culture performed in the 3.5 l medium. Thus, there was 7.5 times more biomass collection in bioreactor compared to classical method. Interpretation \& conclusion: It is postulated that constant culture pH and temperature in the bioreactor extends cultivation time. This could lead to significant increase in parasite numbers. Hence, pH and temperature controllable bioreactors provided acquisition of sufficient amounts of biomass in contrast to classical methods. Therefore, this type of bioreactors may substitute classical culture methods in the production of antigenic molecules for vaccine development.
Keywords: Culture; Leishmania infantum; process development; stirred tank bioreactor; visceral leishmaniasis